2011
DOI: 10.1021/nn103024b
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Quantum Dot−Fatty Ester Stealth Nanoparticles: Toward Clinically Relevant in Vivo Optical Imaging of Deep Tissue

Abstract: Despite broad applications of quantum dots (QDs) in vitro, severe toxicity and dominant liver uptake have limited their clinical application. QDs that excite and emit in the ultraviolet and visible regions have limited in vivo applicability due to significant optical interference exerted by biological fluids and tissues. Hence we devised a new biocompatible hybrid fluorophore composed of near-infrared-emitting PbSe quantum dots encapsulated in solid fatty ester nanoparticles (QD-FEN) for in vivo imaging. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 34 publications
(88 reference statements)
4
49
0
Order By: Relevance
“…As optical imaging is limited by the penetration of light through tissue 22 , the depth of imaging penetration of CF-SPNs is critical for the interrogation of deep, absorbing tissue such as the liver. The depth of imaging penetration following incubation of CF-SPNs with H 2 O 2 was assessed using a tissue-mimicking gel phantom composed of gelatin, hemoglobin, and intralipid 23 . By overlaying various thicknesses of gel phantom, the penetration of the luminescent signal from CF-SPNs was found to be at least 2.5 cm of gel depth (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As optical imaging is limited by the penetration of light through tissue 22 , the depth of imaging penetration of CF-SPNs is critical for the interrogation of deep, absorbing tissue such as the liver. The depth of imaging penetration following incubation of CF-SPNs with H 2 O 2 was assessed using a tissue-mimicking gel phantom composed of gelatin, hemoglobin, and intralipid 23 . By overlaying various thicknesses of gel phantom, the penetration of the luminescent signal from CF-SPNs was found to be at least 2.5 cm of gel depth (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the depth of signal penetration through tissue-like gel phantoms, CF-SPN solution (5μg/mL) in PBS (30 mM, pH = 7.4) was placed in a black 96-well plate. Gel phantoms previously described 23 composed of procine gelatin, bovine hemoglobin, intralipid and NaN 3 in Tris-buffered saline at final concentrations of 10% w/v, 170mM, 1% v/v, and 15 mM, respectively, were overlaid on top of the wells at the desired gel thickness. Images were acquired using an IVIS ™ Spectrum imaging system using chemiluminescence acquisition mode with open filter and autoexposure setting.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, according to the principle of the lowest energy and the reaction kinetics, the balance of reaction was interrupted by the increased temperature and the particle size continually growing larger. Propidium Iodide as fluorescence standards, the quantum yield of these QDs crystals were 50% (530 nm), 30% (580 nm), 40% (590 nm), 35% (625 nm) respectively according to formula (4). The results indicated that the first excitonic peak in the absorption spectrum of CdSe QDs continuously shift to longer wavelengths with increase of temperature, correspondingly.…”
Section: Temperature-controlled Synthesis Of Cdse Qds In Liquid Parafmentioning
confidence: 88%
“…[24] Tris-buffered saline was poured on top of a known amount of sodium azide and gelatin to make a final concentration of 15 mM and 10 w/v%, respectively. The mixture was heated to 50 °C using a water bath under constant stirring.…”
Section: Methodsmentioning
confidence: 99%